Reformulation of Generalized Log-aesthetic Curves with Bernoulli equations. Issue 2 (3rd March 2016) - Miura, Kenjiro T.; Gobithaasan, R. U.; Suzuki, Sho; Usuki, Shin
Abstract: A recent research has found out the relationship between the Log-aesthetic Curve and Riccati differential equations. The obtained differential equations are Riccati, but also Bernoulli type. Based on Sato and Shimizu's derivation of the formula of ρ -shift generalized log-aesthetic curve (GLAC), we derive the formula of the κ -shift GLAC as a solution of a Bernoulli differential equation. GRAPHICAL ABSTRACT: